Analisa Fatwa Berkaitan Akidah Dalam Filem di Malaysia: Sorotan 2005-2018: An Analysis on the Aqidah Fatwas Within Films in Malaysia: A Review From 2005-2018 - Opir, Hajar; Yusof, Muhammed; Siren, Norrodzoh; Abdullah, Luqman; Abdullah, Wan Yusnee (Afkar: Jurnal Akidah dan Pemikiran Islam, 2020)
Film is one of the artistic manuscripts that influences society. Islam, as a merciful religion towards mankind, does not neglect this aspect. In fact, it guides films to comply with the demand of shara‘. The recent development of films focuses on horror stories as a genre so favored by the general that it touches ‘aqidah issues. Therefore, the Fatwa Council plays an important role in tackling this issue to assist those in film industry in producing high quality film and complying with sharia. Hence, this study aims to analyses fatwas in the aspect of ‘aqidah associated to films to see whether the fatwas used are gazette or not. This study is in the form of qualitative. The method used is content analysis through literature review by examining the fatwas made on any related issues in films. The findings show that fatwas related to ‘aqidah in films are significant, however, they are not often discussed by the Fatwa Council in the national or state level.